Investigating Organizational Loyalty in Maritime Companies among Generation X and Millennials Using Partial Least Squares Structural Equa-tion Modeling - Dui, Rayan P.; Paredes, Miguel Paolo L. (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
This study aimed to study job security, social stimulation, and oppor-tunity to use one’s abilities as factors that influenced Gen X (ages 36-54) and Millennial (ages 21 to 35) employees’ organizational loyalty as part of a particular organization. Understanding organizational culture is cru-cial when examining loyalty among Gen X and Millennial seafarers in maritime companies. It has been recognized as a vital factor contributing to the success of business operations. Recently, many initiatives have been implemented to promote workforce development. Employers rec-ognize that their workforce directly affects financial performance, and understanding organizational loyalty across generations is crucial for ensuring this. Sixty seafarers from three Philippine Manning agencies were asked to answer surveys and participate in follow-up interviews as needed to investigate the variables. Partial least squares structural equation modeling (PLS-SEM) and multigroup analysis (PLS-MGA) were used to analyze the gathered respondent data. The findings indicated that social stimulation and the opportunity to use one’s abilities were both groups' most significant predictors of loyalty. The subsequent PLS-MGA showed that job security was particularly a significant predictor for Gen X employees, while it was not a significant predictor for Millennials. The implications show that predictors of loyalty can change depending on the age of the seafarers. Therefore, it is recommended that leaders of the different Philippine manning agencies develop customized strategies for cultivating loyalty from Gen X and millennial employees. must ensure that employees understand a clear path for growth and development, and they should actively pursue these plans. Moreover, management can enhance social connections by forming partnerships and collaborating with maritime stakeholders. This approach can foster positive interac-tions among the various marine stakeholders.